2007
DOI: 10.1021/jo070478m
|View full text |Cite
|
Sign up to set email alerts
|

Structural Revision of Terpenoids with a (3Z)-2-Methyl-3-penten-2-ol Moiety by the Synthesis of (23E)- and (23Z)-Cycloart-23-ene-3β,25-diols

Abstract: Synthesis of (23E)-cycloart-23-ene-3beta,25-diol (1) and its 23Z-isomer 2 was achieved by using cycloartenol as a starting material, thus revising the proposed structure of natural 2 to 1 unequivocally. These synthetic studies revealed that the structural revision (Z-form --> E-form) should also be applied to terpenoids such as (23Z)-3beta-acetoxyeupha-7,23-diene-25-ol, (23Z)-tirucalla-7,23-diene-3beta,25-diol, quadrangularol A, quadrangularic acid K, and daurichromene C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 32 publications
2
43
0
Order By: Relevance
“…The high resolution-electronspray ionization-mass spectra (HR-ESI-MS) displayed a molecular ion peak at m/z 441. 4100 4) Compared with the reported data, 2,4) the stereochemistry of the double bond should be E. The structure of 1 was further confirmed by the single-crystal X-ray diffraction (Fig. 1).…”
Section: )mentioning
confidence: 70%
See 1 more Smart Citation
“…The high resolution-electronspray ionization-mass spectra (HR-ESI-MS) displayed a molecular ion peak at m/z 441. 4100 4) Compared with the reported data, 2,4) the stereochemistry of the double bond should be E. The structure of 1 was further confirmed by the single-crystal X-ray diffraction (Fig. 1).…”
Section: )mentioning
confidence: 70%
“…1) It has not been chemically studied previously. In our current study, four new compounds (1, 2, 6, 7) and three known compounds (3)(4)(5) were isolated from aerial parts of Aphanamixis grandifolia collected from Hainan Province, People's Republic of China. The structures of the new compounds were characterized using spectroscopic methods, and the structure of compound 1 was confirmed by single-crystal X-ray diffraction analysis.…”
Section: Regular Articlementioning
confidence: 94%
“…The signals related to the olefinic protons resulted in a multiplet at δH 5.6 that could not be resolved by obtaining a spectrum of 2 in other deuterated solvents, precluding the straightforward assignment of the geometry of the double bond based on the magnitude of the vicinal coupling constant value. Accordingly, the geometry of the side chain was established as E primarily based on comparison of the 13 C NMR spectroscopic data of analogues with similar side chain [52][53][54] and further backed up by biosynthetic considerations since most related triterpenes isolated from plants display this configuration [55]. Altogether, these data led to characterize the 2D structure of 2 as displayed in Fig.…”
Section: Figure 2 Tablementioning
confidence: 99%
“…Moreover, NOE correlations were observed between H-8 with H-13 but not with H 3 -14, and between H-7 with H 3 -14, indicating that H 3 -14 has a β-orientation. Furthermore, the configuration of the double bond at C-16/C-17 was determined by comparison of the NMR data of 1 in CDCl 3 with those of two related synthetic compounds, (23 E )-cycloart-23-ene-3β,25-diol ( 4 ) and (23 E )-cycloart-23-ene-3β,25-diol ( 5 ) (Figure 4), also measured in CDCl 3 (Table 2) [16]. Comparison of the NMR data of 1 and 4 confirmed that both compounds have the same partial structure from C-15 to C-20 of 1 and from C-22 to C-27 of 4 .…”
Section: Resultsmentioning
confidence: 99%